2010
DOI: 10.1044/1092-4388(2009/09-0023)
|View full text |Cite
|
Sign up to set email alerts
|

Types of Parent Verbal Responsiveness That Predict Language in Young Children With Autism Spectrum Disorder

Abstract: Purpose: This study examined short-term predictive associations between 5 different types of parent verbal responsiveness and later spoken vocabulary for 32 young children with a confirmed diagnosis of autism spectrum disorder (ASD). Method: Parent verbal utterances were coded from videotapes of naturalistic parent–child play sessions using interval and event-based coding. A vocabulary difference score, calculated using the MacArthur Communicative Development Inventories (L. Fenson et al., 1993), was used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
231
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(256 citation statements)
references
References 57 publications
13
231
2
2
Order By: Relevance
“…These findings are consistent with earlier findings showing that JE provides opportunities for additional verbal input when the child and mother are focused on the same activity (e.g., Mundy, Kasari, Sigman, & Ruskin, 1995). When this is the case, vocabulary uptake may be facilitated (McDuffie & Yoder, 2010). Future studies on JE in children with FXS might explore the relationship between object engagement and receptive language as other studies have indicated a positive relationship (Bottema-Beutel et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…These findings are consistent with earlier findings showing that JE provides opportunities for additional verbal input when the child and mother are focused on the same activity (e.g., Mundy, Kasari, Sigman, & Ruskin, 1995). When this is the case, vocabulary uptake may be facilitated (McDuffie & Yoder, 2010). Future studies on JE in children with FXS might explore the relationship between object engagement and receptive language as other studies have indicated a positive relationship (Bottema-Beutel et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…Infants considered at risk would have been those who had experienced one or more of the following conditions prior to 7 months of age: pre-and/or perinatal problems; ear, nose, and throat problems; swallowing/sucking problems; and/or a family history of speech and/or language problems (Brady et al, 2004;Goldstein & Schwade, 2008;McDuffie & Yoder, 2010). See Table 1 Six of the 15 infant participants were male, and nine were female.…”
Section: Participantsmentioning
confidence: 99%
“…In addition, it has been well-documented that caregiver response to early communicative behaviors can be indicative of both typical and atypical development (Brady, Marquis, Fleming, & McLean, 2004;Goldstein & Schwade, 2008;McDuffie & Yoder, 2010 variables for early identification of late-talkers, using mainly expressive language measures such as vocabulary size, has been conducted with parents whose children are as young as 18 to 32 months of age (Rescorla, 2002). Given that caregiver report can be used to reliably track various aspects of development, it seems logical to postulate that caregivers can provide us with a more accurate and functional means of tracking vocal development earlier than previously explored.…”
Section: Tracking Vocal Developmentmentioning
confidence: 99%
“…In this model, parents are explicitly taught to facilitative communication strategies such as recognising the child's non-conventional communicative behaviours, e.g., eye-gaze, body movements (Brady et al 2009) and providing language input that maps the child's focus and interests in contexts that are meaningful (as opposed to artificial) to the child (Brady et al 2009). These features of the minimally intrusive model have been shown to effect in language development such as the advancement of children's vocabulary, morpho-syntax, semantic and pragmatic skills (Wong et al 2012;Camarata et al 1994;McDuffie & Yoder 2010), improved parental language facilitation skills (Girolametto 1988;Kim & Mahoney 2004) and generalisation of intervention outcomes (Goldstein 2002;Roberts & Kaiser 2011). The minimally intrusive model demands that the adults follow the child's lead and adopt the collaborative-consultation approach in early language intervention, rendering it compatible FIGURE 1.…”
Section: Models Of Language Interventionmentioning
confidence: 99%